Biosynthesis Of Endosome-Specific Lipid Bis(Monoacylglycero)Phosphate - Lim,, Shi Rou (2018)
The hypothetical de novo biosynthetic pathway of endosome-specific phospholipid, bis(monoacylglycero)phosphate (BMP) from endogenous phosphatidylglycerol (PG) precursor via lysophosphatidylglycerol (LPG) intermediate had been considered. In the present study, an alternative BMP biosynthetic route from PG via acylphosphatidylglycerol (AcPG) intermediate was proposed. A considerable amount of AcPG was found present in and outside the RAW 264.7 cells during 24 hours of incubation with exogenous PG. A transacylase is required to transfer an acyl chain from a PG donor to a PG acceptor, transforming the acceptor PG into AcPG and the donor PG into LPG.